Effectiveness of Audio-Visual Instructional Methods in Improving English Comprehension Skills among Public Senior Secondary School Students in Kakamega County - Tonny Odhiambo (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Audio-visual instructional methods have become increasingly important in enhancing language learning and comprehension skills in schools. However, limited studies have examined their effectiveness in improving English comprehension skills among public senior secondary school students in Kakamega County, Kenya. This study investigated the influence of educational videos and audio recordings on learners’ listening and reading comprehension skills, while also examining the role of teacher ICT competence and availability of audio-visual resources. The study adopted a descriptive survey research design targeting English teachers and students in public senior secondary schools in Kakamega County. Data were collected using questionnaires, interviews, and observation checklists and analyzed using descriptive and inferential statistics. The findings revealed that educational videos and audio recordings positively improved learners’ English comprehension skills. Teacher ICT competence and the availability of audio-visual resources further enhanced the effectiveness of these instructional methods. The study concludes that audio-visual instructional methods significantly improve English comprehension skills among secondary school learners. The study contributes to existing knowledge by providing empirical evidence on the effectiveness of audio-visual instructional methods within the Kenyan secondary school context. It recommends increased investment in ICT infrastructure, teacher digital training, and provision of adequate audio-visual instructional resources to enhance English language instruction and learner performance.